Impact of LaZnFe2O4 supported NiWO4@D400-MMT@CMS/MMA nanocomposites as a catalytic system in remediation of dyes from wastewater - Safaa. R. Fouda; Salah A. Hassan (Scientific Reports, 2024)
Abstract Herein, a novel nanocomposite based on lanthanum zinc ferrite and nickel tungstate was created by incorporation between (MMT-jeffamine-400) nanoparticles (NPs), chloromethyl styrene as a binder and polymethyl methacrylate monomer using solution polymerization. The as-designed nanocomposites were employed to confiscate xylenol orange “X.O” as an acidic dye and rhodamine B “RhB” as “an amphoteric dye” from colored wastewater. The impact of several parameters such as solution pH, initial dye concentration, the effect of time, and the effect of temperature was explored. The consequences indicated that the pure organoclay had negligible adsorption while that composed of organoclay with PMMA@CMS-polymer incorporated with LaZnFe2O4@NiWO4 particles detached more than 90% for xylenol orange (XO) and 93% for “rhodamine B” molecules. Electrostatic interactions are the predominant factor in the adsorption of cationic and amphoteric adsorbates, as proven by zeta-potential measurement. Additionally, the adsorbent may be regenerate and utilized up to five times with good adsorption capabilities by adding sodium hydroxide. As a result, the removal can be effectively accomplished using the nanocomposite as an adsorbent. The actual and theoretical adsorption capacity values for both dyes at all doses were closely matched, which supported the adsorption kinetics data that fit the pseudo-first order rate model well. The adsorption data’s correlation values (0.995 for XO and 0.98 for RhB) indicated that both dyes’ Langmuir adsorption would perform well. Furthermore, the adsorption of XO and RhB dyes on the adsorbent is confirmed to be a viable reaction by the negative values of ΔGo. The enhanced adsorbent material for the removal of amphoteric and anionic dyes from waste water is the synthesized LaZnFe2O4 supported NiWO4@D400-MMT@CMS/MMA nanocomposites, which exhibits a reusability affinity of up to five cycles.